2013
DOI: 10.1007/978-3-319-01327-5_1
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence, Degradation, and Effect of Polymer-Based Materials in the Environment

Abstract: There is now a plethora of polymer-based materials (PBMs) on the market, because of the increasing demand for cheaper consumable goods, and light-weight industrial materials. Each PBM constitutes a mixture of their representative polymer/sand their various chemical additives. The major polymer types are polyethylene, polypropylene,and polyvinyl chloride, with natural rubber and biodegradable polymers becoming increasingly more important. The most important additives are those that are biologically active, beca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
151
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 159 publications
(168 citation statements)
references
References 244 publications
(209 reference statements)
0
151
0
Order By: Relevance
“…It has been suggested that the term microplastics be redefined as items <1 mm to include only particles in the [40,41], and the term 'mesoplastic' introduced to account for items between 1 and 2,500 mm [42]. Lambert et al [8] described macroplastics as >5 mm, mesoplastics as 5 to >1 mm, microplastics as 1 mm to >0.1 μm, and nanoplastics as 0.1 μm. However, the upper limit of 5 mm is generally accepted because this size is able to include a range of small particles that can be readily ingested by organisms [42].…”
Section: Microplastics As Contaminants Of Emerging Concernmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been suggested that the term microplastics be redefined as items <1 mm to include only particles in the [40,41], and the term 'mesoplastic' introduced to account for items between 1 and 2,500 mm [42]. Lambert et al [8] described macroplastics as >5 mm, mesoplastics as 5 to >1 mm, microplastics as 1 mm to >0.1 μm, and nanoplastics as 0.1 μm. However, the upper limit of 5 mm is generally accepted because this size is able to include a range of small particles that can be readily ingested by organisms [42].…”
Section: Microplastics As Contaminants Of Emerging Concernmentioning
confidence: 99%
“…For instance, Carpenter et al [43], Colton et al [44], and Gregory [45] reported on marine plastics in the 1970s, but they have not been extensively studied particularly in the context of freshwater systems. As research focused on the issue more intensively since the early 2000s, MPs are considered contaminants of emerging concern [8,10,46].…”
Section: Microplastics As Contaminants Of Emerging Concernmentioning
confidence: 99%
See 2 more Smart Citations
“…Additives are incorporated into plastics during plastic production although the quantities used vary greatly. It is estimated that additives account for around 4% of the total weight of plastics produced (Andrady & Neal, 2009;Lambert et al, 2014).…”
Section: 2mentioning
confidence: 99%